Proterozoic to Mesozoic evolution of North-West Africa and Peri-Gondwana microplates: Detrital zircon ages from Morocco and Canada - Marzoli, A.; Davies, J.; Youbi, N.; Merle, Renaud; Dal Corso, J.; Dunkley, D.; Fioretti, A.; Bellieni, G.; Medina, F.; Wotzlaw, J.; McHone, G.; Font, E.; et al. (Elsevier BV, 2017)
© 2017 Elsevier B.V. The complex history of assemblage and disruption of continental plates surrounding the Atlantic Ocean is in part recorded by the distribution of detrital zircon ages entrained in continental sedimentary strata from Morocco (Central High Atlas and Argana basins) and Canada (Grand Manan Island, New Brunswick). Here we investigate detrital zircon from the latest Triassic (ca. 202 Ma) sedimentary strata directly underlying lava flows of the Central Atlantic magmatic province or interlayered within them. SHRIMP (Sensitive High-Resolution Ion MicroProbe) and LA-ICP-MS (Laser Ablation-Inductively Coupled Plasma-Mass Spectrometry) U–Pb ages for zircon range from Paleozoic to Archean with a dominant Neoproterozoic peak, and significant amounts of ca. 2 Ga zircon. These ages suggest a prevailing West African (Gondwanan) provenance at all sampling sites. Notably, the Paleoproterozoic zircon population is particularly abundant in central Morocco, north of the High Atlas chain, suggesting the presence of Eburnean-aged rocks in this part of the country, which is consistent with recent geochronologic data from outcropping rocks. Minor amounts of late Mesoproterozoic and early Neoproterozoic zircon ages (ca. 1.1–0.9 Ga) in Moroccan samples are more difficult to interpret. A provenance from Avalonia or Amazonia, as proposed by previous studies is not supported by the age distributions observed here. An involvement of more distal source regions, possibly located in north-eastern Africa (Arabian Nubian Shield) would instead be possible. Paleozoic zircon ages are abundant in the Canadian sample, pointing to a significant contribution from Hercynian aged source rocks. Such a signal is nearly absent in the Moroccan samples, suggesting that zircon-bearing Hercynian granitic rocks of the Moroccan Meseta block were not yet outcropping at ca. 200 Ma. The only Moroccan samples that yield Paleozoic zircon ages are those interlayered within the CAMP lavas, suggesting an increased dismantling (i.e. uplift) of the Hercynian chain during emplacement of CAMP lava flows, combined with subsidence of the volcanic grabens.